Checklist of Wild Edible Plants of Bihar, India - Fatma, Nasheez; Pan, T.K. (Our Nature, 2013)
Bihar covers 94,163 km2 area but lack floristic information and looking at the high rising value of food and food products, the necessity of nutritive quality and consumption of edible plants cultivated and their wild relatives exploration of different districts of Bihar have been conducted since 2008-2010. The plant species eaten may be whole plant, rhizome, tubers, stem, leaves, inflorescence, fruits, seeds, bark etc. Several times plant parts are used as staple food, while some are used at the time of scarcity like famine, drought etc. Besides, some are well known spices and condiments with good marketable value. Others are used as pickles, drinks, jams and jellies. These plants on large scale are basically identified by the tribal people and introduced in the local markets to earn economy. DOI: http://dx.doi.org/10.3126/on.v10i1.7785